Stress and Coping among College Students during a COVID-19 Red Alert Status on Campus. Issue 3 (4th May 2023) - Samuolis, Jessica; Higley, Emma; Leone, Julia
ABSTRACT: Background: High rates of stress have been found among college students during the COVID-19 pandemic and research on students' use of coping strategies during the pandemic is needed, particularly during periods of extensive restrictions on campus. Purpose: The current study examined stress and coping during a campus red alert at a mid-sized U.S. university. Methods: Data collected from an online survey sent out to undergraduate students 30 days after a COVID-19 red alert status (akin to a campus lockdown) was instituted on a college campus in the Fall of 2020 were analyzed. The survey included scales assessing coping strategies and perceived stress. Results: Regression analyses indicated that stress during the red alert was associated with several maladaptive coping strategies, such as denial, substance use and behavioral disengagement. Whereas stress was inversely associated with positive coping strategies, such as active coping, planning, and acceptance. Discussion: Health education efforts during campus lockdowns should include screening for stress, increased access to mental health services, coping skills-related informational workshops, and virtual recreational and social opportunities. Translation to Health Education Practice: The study highlights how assessing stress and coping among college students during public health events can guide health education activities for college students.